AB0400 Eros study –erosions as rheumatoid arthritis outcomes and biologics. (23rd January 2014) - Cunha-Miranda, L.; Rodrigues, C.; Fernandes, S.
Abstract : Background: In RA, many different clinical and biochemical variables and composite measures reflect the degree of inflammation in the joints. Joint inflammation can lead to joint destruction in most patients. Joint destruction is considered a key outcome in RA and is linked to the worsening of HAQ. One of the claimed breakthroughs of biologic agents is their potential to arrest radiographic progression but is this clinical relevant on the daily practice to consider starting a biologic? Objectives: Assess the main reasons for biologic therapy introduction in RA patients and the relevance of radiological progression on the selection of patients for biological therapies. Methods: Development and implementation of a questionnaire among Portuguese Hospital-based Rheumatologists in order to collect data regarding the reasons they consider important when starting biological therapies in RA patients. This questionnaire also evaluated the impact of radiological progression on starting biological therapy decision Results: 31 rheumatologists answered the questionnaire (about 25-30% of the Portuguese hospital-based rheumatologists); 17 female (55%) with a mean age of 42.7±9.3 years (var: 31-60 years). The mean average time as a specialist was 9.9±7.8 years (var: 1-25 years). The answers to question ``Choose 2 from a total of 6 reasons for prescribing biological therapy'' were: 29 DMARDs failure; 19 maintain disease activity; 3 meets the SPR criteria; 3 radiological progression; 2 physical and psychological disability; 1 young and active patient. When asked about the clinical importance of radiological progression: 11 classified as extremely important; 15 very important, 4 important; 1 less important and 0 answered no importance. Another question included in this questionnaire was ``On the last 100 AR patients observed, in how many times have you assessed the radiological progression through the Total Sharp Score method?'' 25 didn't applied to any patient, 3 applied to 1 patient, 2 applied to 2 patients and 1 applied to 10 patients. So, for a potential number of 3100 patients observed, 17 were evaluated for the radiological damage (0.5%). Conclusions: There is scientifically data demonstrating the importance of radiological progression evaluation; but in the clinical practice this isn't possible. The radiological progression evaluation methods are difficult to apply and time consuming, so they have been losing their relevance in daily clinical practice. The main reasons for the rheumatologist to start biological therapy are increased disease activity and failure of synthetic DMARD's, that are known to been intimately connect with radiological progression. Alternative methods should be developed, such as risk matrices and therapeutic strategies, in order to evaluate radiological progression, allowing a better and adequate management for RA patients. Disclosure of Interest: None Declared